2005
DOI: 10.4161/cbt.4.7.1783
|View full text |Cite
|
Sign up to set email alerts
|

Antisense-mediated downregulation of anti-apoptotic proteins induces apoptosis and sensitizes head and neck squamous cell carcinoma cells to chemotherapy

Abstract: We have earlier reported that the inhibition of apoptosis in head and neck squamous cell carcinomas (HNSCC) is because of upregulated expression of Bcl-2, Bcl-X L and Survivin. Hence, we addressed the question whether antisense approach towards these inhibitors of apoptosis could restore the apoptosis in HNSCC. Further, we wanted to see whether chemotherapeutic efficacy of Cisplatin and Etoposide could be enhanced by using these drugs in combination with antisense oligonucleotides in human laryngeal carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It was shown that transfection of anti-sense Survivin into YUSAC-2 and LOX malignant melanoma cells resulted in spontaneous apoptosis in these cells [90]. The anti-sense approach has also been applied in head and neck squamous cell carcinoma and reported to induce apoptosis and sensitise these cells to chemotherapy [91] and in medullary thyroid carcinoma cells, and was found to inhibit growth and proliferation of these cells [92]. Another approach in targeting Survivin is the use of siRNAs, which have been shown to downregulate Survivin and diminish radioresistance in pancreatic cancer cells [93], to inhibit proliferation and induce apoptosis in SPCA1 and SH77 human lung adenocarcinoma cells [94], to suppress Survivin expression, inhibit cell proliferation and enhance apoptosis in SKOV3/DDP ovarian cancer cells [95] as well as to enhance the radiosensitivity of human non-small cell lung cancer cells [96].…”
Section: Targeting Apoptosis In Cancer Treatmentmentioning
confidence: 99%
“…It was shown that transfection of anti-sense Survivin into YUSAC-2 and LOX malignant melanoma cells resulted in spontaneous apoptosis in these cells [90]. The anti-sense approach has also been applied in head and neck squamous cell carcinoma and reported to induce apoptosis and sensitise these cells to chemotherapy [91] and in medullary thyroid carcinoma cells, and was found to inhibit growth and proliferation of these cells [92]. Another approach in targeting Survivin is the use of siRNAs, which have been shown to downregulate Survivin and diminish radioresistance in pancreatic cancer cells [93], to inhibit proliferation and induce apoptosis in SPCA1 and SH77 human lung adenocarcinoma cells [94], to suppress Survivin expression, inhibit cell proliferation and enhance apoptosis in SKOV3/DDP ovarian cancer cells [95] as well as to enhance the radiosensitivity of human non-small cell lung cancer cells [96].…”
Section: Targeting Apoptosis In Cancer Treatmentmentioning
confidence: 99%
“…This led to decreased cell proliferation and increased caspase-dependent apoptosis in different tumor (lung, sarcomas, lymphomas, thyroid, head, and neck) cell lines [9296]. Furthermore, down-regulation of survivin via AO was shown to enhance sensitivity to cytotoxic agents such as TRAIL [61,63], cisplatin [93], taxol [97], imatinib [98], etoposide [93,99,100], as well as to cytotoxicity induced by radiation therapy [101]. Moreover, treatment with survivin AO resulted in inhibition of tumor growth in murine models [102].…”
Section: Transcriptional Inhibitorsmentioning
confidence: 99%
“…Transfection with the ASO triggered spontaneous apoptosis, and two-colour flow cytometry confirmed decreased endogenous survivin expression. Other pre-clinical studies confirmed these results 47,48 and found that survivin downregulation sensitises certain human cancer cell lines to cisplatin and etoposide, 49 as well as to radiotherapy. 50 LY-2181308 is a second-generation ASO.…”
Section: Translational Inhibitionmentioning
confidence: 62%